The effect of leadership style on employees Welfare (case Study: The employees of Education and instruction office of Tehran province) - زبیده اسکو; نسیم پیرعلائی; احمد علی یزدان پناه (Allameh Tabataba'i University Press, 2016)
the Aim of this study was to explain the more effect of transformational leadership style on employees Welfare (Quality of work life, life satisfaction, Organizational Commitment, and reduction of job burnout) of the Transactional leadership style. Method:This research was conducted in descriptive - Survey Research method. The statistical Population of research included 140 employees of Education and instruction Department of Tehran Province, That 103 member Selected Based on Morgan Table Using Classification a stratified Random Sampling Method. The multifactor Leadership Style (MQL), Quality of Work life(Serji, 2001), Job burnout (Meslej and Jackson, 1981), Organizational Commitment (Maudi, 1979) and Life Satisfaction (Serji, 2001) Questionnaire was used to Collect Data. The Exam of Hypothesis Done With PLS Software. Findings: The Result of structural Equation Showed that Suggested Model Has more Reliability and all the regression in 0.01 level Was significant on both of them affect of Employees Welfare. But the effect of Transformational Leadership style is The most. And this style Due to improve the employees work life Quality and welfare. But the effect of job burnout and organizational commitment and employees life satisfaction isn't significant. Result: Results and Advices about leadership style and employees' welfare in education and instruction office showed that in order to improve Employees Welfare, Managers Must use of Transformational leadership Style.